Status of permanent establishments under GloBE rules - Kuldeep Sharma (South Centre, 2023)
The objective of this Research Paper is to comprehensively identify and analyse all Permanent Establishment (PE) related provisions under the global minimum tax of the Organisation for Economic Co-operation and Development (OECD), which is implemented through the Global Anti Base Erosion (GloBE) Model Rules. The analysis has led to the conclusion that PEs hold a significant position and facilitate application of GloBE Rules. The GloBE Rules have introduced certain new facets involving application of PE provisions when there is no tax treaty; no Corporate Income Tax (CIT) in the source state, and have brought in the concept of stateless PEs. These newly-introduced facets have widened the scope of PEs to enable application of the GloBE Rules in specific situations which would otherwise have remained outside the ambit of taxation. The paper concludes with an observation that the OECD's Inclusive Framework is drafting the provisions of Amount A in a manner that results in consistency with GloBE Rules. Likewise, acceptance of "deemed PE" for GloBE rules should be extended to Amount A as well. By doing so, a tax nexus would be provided in source jurisdictions, which will allow profits attributable to Multinational Enterprises (MNEs) in a digitalized economy (without physical presence) getting taxed under domestic rules of these source (market) jurisdictions. This would have been a much simpler solution and would have eliminated the complexity of Amount A rules to a large extent, as we see today.
Keywords: 300